Influence of diafiltration on flux decline during skim milk ultrafiltration. (December 2018) - Ng, Kenneth S.Y.; Dunstan, Dave E.; Martin, Gregory J.O.
Abstract: The effect of lactose and mineral removal during diafiltration on physicochemical properties of skim milk and flux decline behaviour during ultrafiltration was investigated. Diafiltration mainly resulted in a significant decrease in ionic strength, primarily due to mineral removal. This corresponded to a significant increase in flux, solely due to a decrease in the concentration polarisation resistance (RCP ), which can be attributed to stronger repulsive electrostatic interactions between the retained casein micelles (and whey proteins) in the polarised concentration layer at the membrane surface, resulting in a less densely packed and more permeable particle layer. RCP exhibited a strong correlation with ionic strength in the range of ionic strengths investigated (32–85 mm ). The strong dependence of RCP on ionic strength was considered to remain valid at lower ionic strengths, given the minor impact of more extensive diafiltration on the physical properties of casein micelles previously reported in literature.